Improving Students’ Critical Thinking Skills Through the Application of the Scramble Learning Model - Ismawati; Bakar, Muhammad Abu; Zamroni, M Afif (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
The problem underlying this research is the low level of students’ critical thinking skills. One alternative learning that can be applied to improve students' critical thinking skills is the scramble learning model. This research aims to determine how the scramble learning model can improve students’ critical thinking skills in fiqh subjects. The method used in this study is an experimental method with a pretest-posttest control group design research design. The study was conducted at MTs Negeri 2 Mojokerto. This study uses 2 classes, namely class VII E as an experimental class and class VII H as a randomly selected control class. The instrument used was a critical thinking ability test. In this study, quantitative data were analyzed using statistical analysis of the t-test to see an increase in students’ critical thinking skills. Based on the analysis of students' critical thinking test results obtained, the gain score of the experimental class is higher than the control class, which is 133 for the experimental class and 65 for the control class. After knowing the gain score, an independent sample t test was conducted with the result of a sig (2-tailed) value of 0,000 and smaller than 0,05. Thus it can be concluded that there are significant differences.